Minat Petani Dalam Menggunakan Fungisida Nabati Sebagai Pencegah Penyakit Antraknosa Pada Tanaman Cabai Merah Keriting di Kecamatan Wih Pesam - Harahap, Nurliana; Siregar, Ameilia Zuliyanti; Mude, Miranda Ari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The purpose of this study was to look at the level of interest and the factors that influence it in the use of vegetable fungicides as anthracnose disease prevention in curly red chili plants. This study was carried out from February 2023 to July 2023. Data collection methods included observation, questionnaires that had been tested for validity and reliability and interviews. Methods of data analysis using a Likert scale and multiple linear regression. The results of the study showed that the level of interest of farmers in the use of vegetable fungicides as a prevention of anthracnose disease in curly red chili plants was very high with an interest of 84.71%. The results of multiple linear regression on the factors that influence farmer interest are obtained by the following equation Y = 3.739 - 0.212X1 + 0.057X2 - 0.164X3 + 0.311X4 + 0.235X5 + 0.381X6. Simultaneously the variables of age, farming experience, land area, role of extension workers, community environment, and facilities and infrastructure have a joint effect on farmers' interests. Partially the variables of age, land area, role of extension workers, community environment, and facilities and infrastructure have a significant effect, while the variable farming experience has no significant effect.